Optimization of Culture Conditions to Produce Thermostable Keratinolytic Protease of Brevibacillus thermoruber LII, Isolated from the Padang Cermin Hot Spring, Lampung, Indonesia - DEWI SESWITA ZILDA; ENI HARMAYANI; JAKA WIDADA; WIDYA ASMARA; EKO IRIANTO; GINTUNG PATANTIS; YUSRO NURI FAWZYA (Microbiology Indonesia, 2012)
Hot springs  represent one of  the most promising  sources  for  the  isolation of  thermostable enzyme producers.  The microorganisms living in a hot spring not only have to withstand elevated temperatures but also extreme environmental pH and certain chemical compounds that are often toxic to other microbes. A bacterial strain denoted  as  Brevibacillus  thermoruber  LII  has  been  isolated  from  Padang  Cermin  Hot  Spring,  Lampung,  Indonesia. Optimization of  the conditions  for protease production by  this strain  revealed  that  the  isolate produced a thermostable protease optimally at temperature and pH ranges 45-55  C and 6-7, respectively, with keratin as substrate. The strain’s keratinolytic activity was shown by the ability to degrade untreated chicken feathers after 24 h  incubation  in  liquid medium.